(untitled) (Canadian Medical Education Journal, 2026)
Implication Statement The start of independent clinical practice is an exciting—but often daunting—milestone for newly minted physicians. To better support practice readiness, our postgraduate training program created a learner-centered, longitudinal transition-to-practice curriculum for final-year residents. The curriculum covers a spectrum of key early career topics, which are delivered through diverse educational formats. While nothing can completely prepare new practitioners for their first months of independent practice, we hope our approach offers valuable insights for other centres helping trainees to navigate this professional threshold with greater confidence.